A 3D Empirical Model of Electron Density Based on CSES Radio Occultation Measurements - He Huang; Jian Lin; Song Xu; Huijun Le; Feng Guo; Zhima Zeren; Libo Liu; Xuhui Shen (Space Weather)
Abstract China Seismo‐Electromagnetic Satellite (CSES) was successfully launched in February 2018. About 280 thousand ionospheric radio occultation (RO) electron density profiles (EDP) have been accumulated till the end of 2020. The CSES is a Sun‐synchronous orbit satellite with descending and ascending nodes around 14:00 and 02:00 LT, respectively, at the height of 507 km. Thus, most of the RO EDP concentrate on these two local time bins. First, we constructed empirical NmF2, hmF2, and Hm models at two local time windows 14:00 and 02:00 LT, respectively. The three models describe that NmF2, hmF2, and Hm vary with solar activity, season, longitude, and latitude. Through the comparison with CSES observations, the NmF2, hmF2, and Hm models could reproduce the physical characteristics rather well. Then, according to Chapman profile function, a EDP model was reconstructed based on the NmF2, hmF2, and Hm models, named CSES_Ne‐Profile Model. To evaluate the model performance, we simulated the COSMIC‐2 observations by CSES_Ne‐Profile Model and international reference ionosphere (IRI) model respectively. The results show that CSES_Ne‐Profile Model precedes the IRI model. Additionally, our model captures the merging phenomenon of the two peaks of equatorial ionospheric anomaly, which is missed by IRI. Further, CSES_NePrf model is a useful tool to provide the quiet background for case studies and joint studies with other payloads onboard CSES.